Expanding the 'aplysinospin cascade' through DNA-templated [2+2] photocycloaddition. Issue 28 (20th March 2023) - Oger, Samuel; Duchemin, Nicolas; Bendiab, Yara Mayssa; Birlirakis, Nicolas; Skiredj, Adam; Rharrabti, Somia; Jullian, Jean-Christophe; Poupon, Erwan; Smietana, Michael; Arseniyadis, Stellios; Evanno, Laurent
Abstract : We report here a general and scalable method for the synthesis of cyclobutane-containing natural products and analogues thereof via a DNA-templated [2+2] photo-induced homo- and heterodimerization of aplysinopsins. Abstract : Inspired by the unique ability of nucleic acids to template chemical transformations that are otherwise impossible in solution, we embarked on the generalisation of our DNA-templated [2+2] photo-induced homo- and heterodimerization of aplysinopsins. Our process ensures a straightforward access to cyclobutane containing natural products and analogues thereof. Most importantly, this conceptual biomimetic achievement presents interesting arguments to build a biosynthetic scenario.